Fashion museum on the web: access and information of heritage collections in online catalogs (ModaPalavra e-periódico, 2015)
This article is about informations of heritage of fashion museums in the web.It presents analyses based on categories of Museum and Web Awards and other questions focused on costume, 33 institutional websites were researched to provide material for it.As a result of this work is provided a structural scripted and proposals for registration of objects of clothing material culture. The informations and reflections result as a contribution to the approach of the history of costume objects, by their material and imaterial elements.
Keywords: museums; websites; costume museums; material culture; costume